PENGARUH TIONGKOK TERHADAP KEBIJAKAN EKONOMI POLITIK ZIMBABWE DALAM MENERAPKAN YUAN SEBAGAI MATA UANG RESMI - Boris Romario Napitupulu; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Using the study of international political economy, a country which has a big economic power, in this case China, may affect the international system, particularly affecting poor countries. China has played an important role in the system of governance and the economy in Zimbabwe, a country located area of Africa. At the moment Zimbabwe is experiencing economic slump since 2008 and trade relations with Western countries stopped, the Chinese appear to be a Zimbabwe‟s trading and political partner to curb the sanction of the international community to Zimbabwe. The political crisis was also experienced by Zimbabwe, by the announcement of the Zimbabwe Democracy and Economic Recovery Act (ZDERA) by the United States and European countries. But China actually use his voting rights in the UN Security Council to block sanctions. China's next role is to help the economy of Zimbabwe by offering fresh loans, credit facilities, investment projects, and a wide range of economic cooperation. The offer was made because China has a great power in the global financial structure, in which China has the largest foreign exchange reserves compared with any country. Hyperinflation that occurred resulted in Zimbabwe should abandon its currency can no longer be used. This makes the Zimbabwean government introduce the use of multiple currencies in 2009. doubted the consistency and stability of the dollar as an international currency, making China's yuan currency offer alternatives as a means of international trade transactions. It underlies the Chinese government's desire to control credit creation in the international economy as a base to dominate the world economy.Keywords : Influence, Hyperinflation, China, Zimbabwe, Yuan